1998
DOI: 10.1083/jcb.141.6.1407
|View full text |Cite
|
Sign up to set email alerts
|

OCI-5/GPC3, a Glypican Encoded by a Gene That Is Mutated in the Simpson-Golabi-Behmel Overgrowth Syndrome, Induces Apoptosis in a Cell Line–specific Manner

Abstract: OCI-5/GPC3 is a member of the glypican family. Glypicans are heparan sulfate proteoglycans that are bound to the cell surface through a glycosyl-phosphatidylinositol anchor. It has recently been shown that the OCI-5/GPC3 gene is mutated in patients with the Simpson-Golabi-Behmel Syndrome (SGBS), an X-linked disorder characterized by pre- and postnatal overgrowth and various visceral and skeletal dysmorphisms. Some of these dysmorphisms could be the result of deficient growth inhibition or apoptosis in certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
118
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 41 publications
9
118
1
1
Order By: Relevance
“…Further investigation may reveal the relationship of this regenerative phenomenon to the molecular biology of hepatocellular carcinoma. Although GPC3 was originally identified as a suppressor of cell proliferation, 21,22 it also acts as a negative regulator of inhibitory growth factors such as BMP-7. 20,23 Intracellular distribution of GPC3 might be related to such an altered function.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation may reveal the relationship of this regenerative phenomenon to the molecular biology of hepatocellular carcinoma. Although GPC3 was originally identified as a suppressor of cell proliferation, 21,22 it also acts as a negative regulator of inhibitory growth factors such as BMP-7. 20,23 Intracellular distribution of GPC3 might be related to such an altered function.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that membranebound GPC3 induces programmed cell death in cell lines derived from a rat MM and a human breast cancer (Gonzalez et al, 1998). Induction of apoptosis is cell line-speci®c, because such a response was not elicited in human HT-29 colorectal tumor cells or NIH3T3 ®broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Hemagglutinin (HA) epitope-tagged human GPC3 cDNA was cloned into pEF-BOS vector (Gonzalez et al, 1998). Vector alone was used as a control.…”
Section: Ectopic Expression Of Gpc3 In Human MM Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ± 8 The exaggerated growth is probably due to an imbalance between growth-promoting and growth-inhibitory factors at speci®c early developmental stages, resulting in defective growth inhibition or apoptosis in certain cell types. 23,24 Recently, a mutation in the gene encoding for glypican 3 was detected in a minority of patients with SGBS. 10 Glypican-3 is a cell-surface proteoglycan which is involved in the control of organ growth.…”
Section: Discussionmentioning
confidence: 99%